Empowermen for Women Who Stay in Australia In Parenting at Multicultural Contex - Yufiarti; Lara Fridani; Gusti Devi Artanti; Cucu Cahyana; Irma Rosalinda; Fildzah Rudyah Putri (Bahasa Indonesia, 2022)
ABSTRACT The aim of current community service is to empower Indonesian women living in Australia in knowledge of multicultural education and care in a multicultural context. The problems faced by Indonesian women living in Australia are very complex, starting with the goal of going to Australia, mobility, educating their children in different cultures to dealing with children's problems and themselves. This service was carried out for two years. The approach taken is to provide parenting training in a multicultural context. The duration to conduct this research will be two years by stages. In the first year of study, the followings processes will take place namely identification, training, counseling and evaluation. final stages of publication (journals and proceedings). In the second years: (1) recommendation, (2) Focus Group Discussion, and publication. The resulting output is: 1) The implementation of women's empowerment activities in parenting in multicultural context. 2) Multicultural education guidelines for mothers. 3) Certificates for participants who take part in the activity. This study will resulting; a) Published paper in national journal, b) Online media publication, c) Video uploaded on Youtube, and d) Webinar event held in Australia using an online platform. The community service implemented on Junne 2021 followed by 31 members. The activities doing well such Focus Discussion, counseling and evaluation. Based on the result of instrumen the mothers interest on the subject matter. They are sutiesfied of this activities. They need this activities again for other subject such as cooking theme.